The Role of Age in the Relationship between Mindfulness and Emotion Regulation in Adults - Yuniar, Yuniar; Boediman, Lia Mawasari; Mansoer, Winarini Wilman D. (Jurnal Sains Psikologi, 2024)
This research aims to investigate the role of age as a moderator in the contribution of mindfulness to emotion regulation abilities in adults in Indonesia. This research used a quantitative approach with a total number of 234 partici pants, consisting of 81 young adults and 153 middle adults, with a mean score of 43.33. Data were collected using the Difficulties in Emotion Regulation Scale-Short Form (DERS-SF) and Mindfulness Attention Awareness Scale (MAAS) questionnaires, which were distributed online. The research results show that adult individuals with low levels of mindfulness have low emotional regulation abilities, and age does not play a role as a moderator in the role of mindfulness on emotional regulation abilities. The uneven distribution based on participant domicile is a limitation that needs to be considered in future research.